Epigenetic instability and hypofunctionality of fetal Tregs allow a permissive regulatory environment for T effector memory maturation - Jing Yao Leong; Naomi McGovern; Archita Mishra; Martin Wasser; Pavanish Kumar; Shi Huan Tay; Sharifah Nur Hazirah; Joo Guan Yeo; Xiu Qi Tan; Nursyuhadah Sutamam; Farah Nadiah Azman; Camillus Jian Hui Chua; et al. (Proceedings of the National Academy of Sciences, 2025)
The human gestational environment is commonly perceived to be predominantly suppressive and incompatible for T effector maturation. However, evidence of a competent effector fetal environment is mounting in the field. Here, we employed a high parametric, mass cytometry–based approach to study the fetal circulatory and microenvironmental immunomes, with the aim to understand the inception and extent of fetal effector T cell priming and its relation with regulatory mechanisms. We found evidence of fetal thymic immune imprinting, coupled with both circulatory and tissue effector memory development. Correspondingly, in the regulatory compartment, we detected the presence of Tbet + Treg in fetal tissues at elevated levels compared to adult tissues. Fetal Tregs, though capable of suppression, were hyposuppressive as compared with adult counterparts. We found that a proportion of fetal Tregs lost FoxP3 commitment during proliferation and exhibited higher TCR clonotype sharing with effector T cells, indicating higher plasticity in fetal Tregs than adult. Epigenetic profiling of the FoxP3 promoter locus reveals that fetal Tregs were only partially demethylated, possibly explaining the observed instability. In summary, our data provide evidence of a regulatory environment in the 2nd trimester permissive for T effector maturation, in part contributed by the relative instability and hypofunctionality in fetal Tregs.